Adult Age Differences in Sensitivity to Semantic Satiation. Issue 2 (15th March 2023) - Black, Sheila R.; Wood, Meagan M.; Choi, Jaimie; Jackson, Barbara-Shae; Evans, Teairra Z.
ABSTRACT: Objective: In this study, we investigated age differences in sensitivity to semantic satiation.Semantic satiation was conceptualized as occurring within a semantic activation framework. Method: A prime or to-be-satiated word (e.g., ANIMAL) was presented repeatedly for an average of 2.5, 12.5, or 22.5 times. Afterward, a word triad comprised of two related words (e.g., PURPLE, YELLOW) and one unrelated word (e.g., DOG) was presented. The two related words were designated as nontargets or context words in the display and the unrelated word was the target. Participants were instructed to indicate as quickly and as accurately as possible which of the words in the triad was the unrelated word by pressing a key which was spatially compatible to the position of the stimulus on the CRt. Results: For young but not older adults, there was an attenuation of priming effects in the response latency data as repetition of the prime increased. Conclusion: These results were interpreted as evidence that older adults are less sensitive to the semantic satiation phenomenon than young adults.